2014
DOI: 10.1053/j.semtcvs.2014.09.002
|View full text |Cite
|
Sign up to set email alerts
|

The New IASLC-ATS-ERS Lung Adenocarcinoma Classification: What the Surgeon Should Know

Abstract: In 2011, a new histologic classification of lung adenocarcinomas was proposed from a joint working group of the International Association for the Study of Lung Cancer (IASLC), American Thoracic Society (ATS), and European Respiratory Society (ERS), based on the recommendation of an international and multidisciplinary panel. This classification proposed a method of comprehensive histologic subtyping (lepidic, acinar, papillary, micropapillary, and solid pattern) based on semi-quantitative assessment of histolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
72
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 58 publications
(77 reference statements)
1
72
1
1
Order By: Relevance
“…Prior studies have shown outcomes of 100% RFS after surgical resection for AIS and MIA, and among the five subtypes of adenocarcinoma, lepidic adenocarcinoma showed the most favorable prognosis (14,15). Some reports also determined that the degree of lepidic pattern in a tumor was related to disease prognosis, where greater than 50% lepidic pattern was a favorable prognostic indicator in cases of invasive adenocarcinoma (16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have shown outcomes of 100% RFS after surgical resection for AIS and MIA, and among the five subtypes of adenocarcinoma, lepidic adenocarcinoma showed the most favorable prognosis (14,15). Some reports also determined that the degree of lepidic pattern in a tumor was related to disease prognosis, where greater than 50% lepidic pattern was a favorable prognostic indicator in cases of invasive adenocarcinoma (16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…One of those indications is for nodules with greater than 50% GGO appearance on CT. Moreover, two ongoing studies (JCOG 0802, JCOG 0804) have also adopted C/T ratio to select sublobar resection (14,22). Clinically, it is practical for thoracic surgeons to use the C/T ratio to classify nodules on CT as GGO-predominant or solid-predominant.…”
Section: Discussionmentioning
confidence: 99%
“…One recent study using a national cancer database in the United States demonstrated that patients who underwent sublobar resection for stage IA NSCLC had poorer oncologic outcomes (14). However, some studies reported that patients who had sublobar resection for stage IA NSCLC presenting as a GGO nodule had similar oncologic outcomes (6,7,15). Therefore, it might be possible that sublobar resection is suitable for selective cases.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we evaluated RFS instead of overall survival because with stage I disease, more patients succumbed to other causes than from cancer during the follow-up period (7). Further, RFS is a more accurate measurement of survival, as it reflects the biological behavior of the cancer rather than death secondary to unrelated factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation